2017
DOI: 10.1016/j.nepig.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting roles for DNA methyltransferases and histone deacetylases in single-item and associative recognition memory

Abstract: Recognition memory enables us to judge whether we have encountered a stimulus before and to recall associated information, including where the stimulus was encountered. The perirhinal cortex (PRh) is required for judgment of stimulus familiarity, while hippocampus (HPC) and medial prefrontal cortex (mPFC) are additionally involved when spatial information associated with a stimulus needs to be remembered. While gene expression is known to be essential for the consolidation of long-term recognition memory, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Interestingly, a reduction in novel object preference and increased variability was observed in our drug-treated normal care animals ( M = 61.69, SD = 10.63), as about half the subjects in this group did not exhibit a novel object preference while all of the vehicle-treated normal maternal care animals did exhibit a preference. The lack of NOR performance in some of the zebularine-treated normal maternal care animals is consistent with a previous report finding an impairment in NOR in normal animals after administration of a DNMT inhibitor (Scott et al, 2017 ). Future research is warranted to elucidate the reasons for the variability in NOR performance and the effect, if any, of zebularine treatment and exposure to maltreatment on the ability to perform NOR in individual subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a reduction in novel object preference and increased variability was observed in our drug-treated normal care animals ( M = 61.69, SD = 10.63), as about half the subjects in this group did not exhibit a novel object preference while all of the vehicle-treated normal maternal care animals did exhibit a preference. The lack of NOR performance in some of the zebularine-treated normal maternal care animals is consistent with a previous report finding an impairment in NOR in normal animals after administration of a DNMT inhibitor (Scott et al, 2017 ). Future research is warranted to elucidate the reasons for the variability in NOR performance and the effect, if any, of zebularine treatment and exposure to maltreatment on the ability to perform NOR in individual subjects.…”
Section: Discussionsupporting
confidence: 92%
“…From our previous studies initiation of this cellular pathway appears to depend on the activation of specific receptor subtypes in the mPFC such as the NMDA and D1/D5 receptor and blockade of these receptors impairs both object-in-place Warburton 2008, 2011b;Savalli et al 2015), and temporal order memory (Hotte et al 2006) and interestingly activation of the NMDA and D1/D5 receptors has been shown to be crucial for CREB phosphorylation (Pittenger et al 2002;Hotte et al 2006;Olianas et al 2012;Kirschmann et al 2014;Nygard et al 2017). CREB expression is regulated at transcriptional level by epigenetic mechanisms such as DNA methylation (Chahrour et al 2008) and we have shown that disruption of DNA methylation impairs longterm object-in-place memory (Chahrour et al 2008;Scott et al 2017). Hence there are direct links between receptor activation, CREB-mediated cellular processes and gene expression in the mPFC, that leads to the long-term associative and temporal order recognition memory formation.…”
Section: Discussionmentioning
confidence: 98%
“…The processing of OiP memory requires the participation of the mPFC, as evidenced by studies of lesions or blocking of glutamate-, acetylcholine (ACh)-or dopamine (DA)-R (Barker et al, 2007;Barker and Warburton, 2008, 2009, 2015Savalli et al, 2015). In addition, medial prefrontal cortical DNA methylation, but not histone deacetylation, is involved in OiP memory (Scott et al, 2017). Thus, the medial prefrontal cortical DNA methylation, glutamate, ACh and DA systems mediate the recognition of specific objectplace relationships.…”
Section: The Role Of the Medial Prefrontal Cortexmentioning
confidence: 99%